Dscam1 overexpression impairs the function of the gut nervous system in Drosophila. Issue 1 (12th December 2022) - Hernández, Karla; Godoy, Luis; Newquist, Gunnar; Kellermeyer, Riley; Alavi, Maryam; Mathew, Dennis; Kidd, Thomas
Abstract: Background: Down syndrome (DS) patients have a 100‐fold increase in the risk of Hirschsprung syndrome of the colon and rectum (HSCR), a lack of enteric neurons in the colon. The leading DS candidate gene is trisomy of the Down syndrome cell adhesion molecule (DSCAM). Results: We find that Dscam1 protein is expressed in the Drosophila enteric/stomatogastric nervous system (SNS). Axonal Dscam1 phenotypes can be rescued equally by diverse isoforms. Overexpression of Dscam1 resulted in frontal and hindgut nerve overgrowth. Expression of dominant negative Dscam1‐ΔC led to a truncated frontal nerve and increased branching of the hindgut nerve. Larval locomotion is influenced by feeding state, and we found that the average speed of larvae with Dscam1 SNS expression was reduced, whereas overexpression of Dscam1‐ΔC significantly increased the speed. Dscam1 overexpression reduced the efficiency of food clearance from the larval gut. Conclusion: Our work demonstrates that overexpression of Dscam1 can perturb gut function in a model system. Key Findings: Manipulation of Dscam levels in the Drosophila stomatogastric nervous system leads to longer, expanded axons (overexpression) or shorter, more branched axons (inhibition). Functional effects are correlated with level manipulation. Dscam1 is expressed in the Drosophila gut nervous system. Dscam1 overexpression leads to enteric axon overgrowth. Dscam1 overexpression reduces larval locomotion and leads to defecation defects. Inhibition of Dscam1 reduces axon growth.